2021
DOI: 10.3897/pharmacia.68.e66693
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fatty acid composition content in the plant components of antidiabetic herbal mixture by GC-MS

Abstract: Medical plants and their combinations due to the wide range of biologically active substances can influence on various links of the pathogenetic mechanism of development of diabetes mellitus and its complications. One of such combinations is an anidiabetic herbal mixture (Urtica dioica L. leaf, Rosa majalis L. fruits, Vaccinium myrtillus L. leaf, Mentha piperita L. herb and Taraxacum officinale L. roots) with established hypoglycemic, hypolipidemic, antioxidant, hepatoprotective, pancreatoprotective activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Savych et al reported on the leaves of bilberry saturated fatty acids (palmitic acid in major quantity) and polyunsaturated acids (linoleic and linolenic) [ 8 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Savych et al reported on the leaves of bilberry saturated fatty acids (palmitic acid in major quantity) and polyunsaturated acids (linoleic and linolenic) [ 8 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Following this selection, 64 publications remained, and the distribution over the 10 years is represented in Figure 1 . Some of these publications (six research articles) reported the pharmacological action or bioactive compounds of polyherbal formulations/plant mixtures [ 7 , 8 , 9 , 10 ], and Ieri et al reports results for the analysis of the bud extract of bilberry [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antidiabetic (Bharti et al, 2018); (Savych et al, 2021), alpha-amylase inhibitors and antioxidant (Ahmed & Ashiq 2014)…”
Section: Identified Compoundsmentioning
confidence: 99%
“…In addition, herbal medicines, as a rule, have a wide range of pharmacological properties, which is realized through different groups of phytochemicals (Oh and Jun 2014;Kooti et al 2016;Budniak et al 2020;Marchyshyn et al 2020). Combinations of different medicinal plants deserve special attention as such herbal mixtures will have more biologically active substances that will affect all parts of the pathogenetic mechanism of diabetes mellitus and its complications (Savych et al 2020a(Savych et al , 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…One of such combinations is an antidiabetic herbal mixture (Urticae folia, Rosae frucrus, Myrtilli folia, Menthae folia and Taraxaci radices) with established hypoglycemic, hypolipidemic, antioxidant, hepatoprotective, pancreatoprotective activity in pharmacological study in vivo (Savych et al 2020b(Savych et al , c, d, e, f, 2021d and the defined phytochemical composition that determines such pharmacodynamics (Savych et al 2020a(Savych et al , 2021a.…”
Section: Introductionmentioning
confidence: 99%